2013
DOI: 10.11604/pamj.2013.14.10.1373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with percutaneous injuries and splash exposures among health-care workers in a provincial hospital, Kenya, 2010

Abstract: IntroductionAccidental occupational exposure of healthcare workers to blood and body fluids after skin injury or mucous membrane contact constitutes a risk for transmission of blood-borne pathogens. Such pathogens include Human Immunodeficiency Virus (HIV), Hepatitis B virus (HBV) and Hepatitis C virus (HCV). We conducted a study to determine the prevalence and associated factors for percutaneous injuries and splash exposures among health-care workers in Rift Valley provincial hospital.MethodsA cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
118
9
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 20 publications
23
118
9
6
Order By: Relevance
“…In concordance to our findings, some studies have reported female HCWs being the most common group to be affected by NSI, probably nurses (Clarke et al, 2002 andMbaisi et al, 2013). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In concordance to our findings, some studies have reported female HCWs being the most common group to be affected by NSI, probably nurses (Clarke et al, 2002 andMbaisi et al, 2013). …”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to the study done in India 2017 reporting that blood sample collection was the most common procedure during which NSI occurred (Goel et al, 2017). This is in contrast to many other studies where stitching was the most common procedure (29-46%), followed by blood sample collection (19%) responsible for NSI (Cervini andBell, 2005 andMbaisi et al, 2013). Our explanation of this difference is the availability of better facilities.…”
Section: Discussioncontrasting
confidence: 69%
“…In other terms, approximately 30 NSIs per 100 beds per year are reported for an average hospital (6). Some factors that have been found to be independently associated with exposure to BBFs and NSIs include male gender, an age below 40 years (7), the recapping of needles (8), work experience of less than two years (9), and working at a surgical ward (10). Inadequate human and other resources and high emotional exhaustion significantly increase the risk of occupational exposure to BBFs (11).…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate human and other resources and high emotional exhaustion significantly increase the risk of occupational exposure to BBFs (11). The presence of a health office for HCWs at a hospital, work at a university hospital, and previous training on infection control measures are associated with lower levels of NSIs and/or sharp injuries (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…O maior número de acidentes ocorre durante a realização de procedimentos, cuidados ao paciente no leito como punção venosa, aspiração e administração de medicamentos. As literaturas nacionais e internacionais apontam que as mãos foram a parte do corpo mais envolvida em acidentes (Mbaisi et al,2013;Gomes et al,2009;Spagnuolo, Baldo, Guerrini, 2008).…”
Section: O Trabalhador De Enfermagem E O Acidente Com Fluido Biológicounclassified